KINERJA KOMISI PEMILIHAN UMUM DAERAH PROVINSI RIAU DALAM MENGELOLA INFORMASI PADA PENYELENGGARAAN PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR RIAU PADA PUTARAN PERTAMA TAHUN 2013 - Perdana, Angga; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research titled âperformance of provincial electoral commission Riau in managing information on the implementation of election of the governor and deputy governor of Riau in the first round of 2013â. Purpose of this study is to know how the performance of provincial electoral commission Riau in managing information on the conduct of elections for governor and deputy governor of Riau. This research uses qualitative descriptive method. Data collected by observation and interview. Of the results of this research is that performance of provincial electoral commission Riau in managing information on the conduct of elections for governor and deputy governor of Riau in the first round of 2013 can be seen through several stages of, management information on the stages of the selection list remains, management information on the stages of registration, verification and determination of the candidate pairs, management of information on the phase of socialization,management of information on the phase of the campaign, management information on the voting stage, management information on the stages of counting and management information on the stages of the determination of the selected pair. of one of these stages still have shortage but what has been done by local election commissions Riau was based on procedures.It is concluded that the performance of local election commissions in Riau in managing information on the conduct of elections for governor and deputy governor of Riau in the first round of 2013 good enough.Key world : Performance, Local Election Commission, Information Management